FROM STATIC DISPLAYS TO INTERACTIVE AR: EVALUATING THE EFFECTIVENESS OF AN AR APP FOR GEN Z AND ALPHA IN MUSEUM PUSAKA - REHMAN ULLAH, KHAN; Yin Bee, Oon; Amalia, Madihie; Ida Juliana, Hutasuhut; Hardyman, Barawi (Little Lion Scientific, 2025)
Museums play a crucial role in preserving and disseminating cultural heritage; however, they often struggle to engage modern audiences who seek immersive and interactive experiences. Traditional static displays fail to engage visitors or transfer cultural values to the new generations, specifically the Gens Z and Alpha. This research explores the implementation of Augmented Reality (AR) in museum settings to enhance visitor engagement and learning effectiveness, with a particular focus on the Museum Pusaka at Taman Mini Indonesia Indah in Jakarta. An applied empirical research design was utilized, two different studies involving a total of 40 and 86 students who were divided into a control or an experimental group. The experimental group used an AR mobile application that contains 3D models and interactive content, while the control group used traditional printed materials. To measure the learning outcomes and engagement, pre-and post-tests were conducted, and the data were analysed and compared using paired sample t-tests and ANCOVA. The results showed significant improvements in both learning and engagement among participants using the AR mobile application. These findings indicate that AR has the potential to transform the museum exhibit more engaging, interactive, and impactful.